2021
DOI: 10.1021/acs.langmuir.1c02032
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Defect Density in UiO-66 Frameworks for Enhanced Pb(II) Adsorption

Abstract: Defect engineering of metal organic frameworks offers potential prospects for tuning their features toward particular applications. Herein, two series of defective UiO-66 frameworks were synthesized via changing the concentration of the linker and synthetic temperature of the reaction. These defective materials showed a significant improvement in the capability of Pb­(II) removal from wastewater. This strategy for defect engineering not only created additional active sites, more open framework, and enhanced po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…In all the studies performed, the reference adsorbent UiO-66-0FA had the lowest Q max , further confirming previous conclusions on the role of defects and/or the carboxyl functional groups on the linker as adsorption sites. This is further confirmed in previous studies that showed the effect of the increase in the defect number on the increased Pb­(II) adsorption in UiO-66 adsorbents . In fact, the UiO-66-0FA sample shows a similar Q max of Pb­(II) compared to previously synthesized UiO-66 samples with HCl as a modulator (48.7 mg/g), while it performed much better than a sample synthesized to have as little as 0.1 defects per cluster (19.4–25.5 mg/g) .…”
Section: Resultssupporting
confidence: 87%
“…In all the studies performed, the reference adsorbent UiO-66-0FA had the lowest Q max , further confirming previous conclusions on the role of defects and/or the carboxyl functional groups on the linker as adsorption sites. This is further confirmed in previous studies that showed the effect of the increase in the defect number on the increased Pb­(II) adsorption in UiO-66 adsorbents . In fact, the UiO-66-0FA sample shows a similar Q max of Pb­(II) compared to previously synthesized UiO-66 samples with HCl as a modulator (48.7 mg/g), while it performed much better than a sample synthesized to have as little as 0.1 defects per cluster (19.4–25.5 mg/g) .…”
Section: Resultssupporting
confidence: 87%
“…Prior to the batch adsorption experiments, the compositions of the materials, for instance, Fc 1 -MIL-100(Fe), Fc 2 -MIL-100(Fe), and Fc 4 -MIL-100(Fe), were compared with their removal efficiency. After the selection of the optimized material, the effects of adsorption conditions were evaluated with the added amounts of materials (10, 20, 30, 40, and 50 mg), adsorption times (20,40,60,120,180,240,300,360,480, 600, 720, and 1440 min), and adsorption temperatures (283, 293, 303, 313, and 323 K). In addition, the effects of pH (2.0, 4.0, 6.0, 8.0, 10.0, and 12.0) and coexisting ions (20 mM Cu 2+ , Cd 2+ , Pb 2+ , NO 3 − , CI − , and H 2 PO 4 − ) on the removal efficiencies (REs) of Cr(VI) and imidacloprid were also researched.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Meng et al used a nitrogen-doped MoS 2 nanoflower to effectively remove Cr­(VI) . Ali et al prepared defective UIO-66 to adsorb Pb­(II) in wastewater . Yang et al studied the effect of pH on the adsorption of pesticide at black carbon as adsorbents .…”
Section: Introductionmentioning
confidence: 99%
“…inorganic cations and organic linkers (10). Such materials have quickly moved to the forefront of materials research due to their extraordinary internal surface areas and porosity, chemical stability, and surface capability to selectively capture of guest species (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Accordingly, MOFs can be used in many applications such as gas storage, separation, catalysis, sensing, drug delivery, biological and proton conduction.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are recognized to be considerably superior adsorbents as compared to conventional materials such as activated carbons and zeolites (14). Among various MOFs, UiO-MOF formulations (UiO-66, UiO-67, UiO-68, and UiO-69) have superior stability in different chemical media with large porosity (11,(16)(17)(18)(19)(20)(21). Thus they can be emerged as effectively adsorbents for removal of heavy metal ions from a variety of wastewater samples (11,16).…”
Section: Introductionmentioning
confidence: 99%